VC An American History - Nicholas, Tom (Harvard University Press, 2019)
From nineteenth-century whaling to a multitude of firms pursuing entrepreneurial finance today, venture finance reflects a deep-seated tradition in the deployment of risk capital in the United States. Tom Nicholas's history of the venture capital industry offers a roller coaster ride through America's ongoing pursuit of financial gain